Content prioritisation of the College of Emergency Medicine specialty curriculum: an exploratory study using a modified Delphi approach. Issue 3 (20th February 2009) - Clancy, M; Kilroy, D; Driscoll, P
Abstract : Aims: To determine opinion in relation to prioritisation of topics within the clinical curriculum of the College of Emergency Medicine. Methods: A modified iterated Delphi technique was used employing a participant panel of 40 randomly selected consultants in emergency medicine. Free text was used in order to generate issues for opinion. Likert scales were then employed to refine this opinion. Results: The overall response rate was 50%. Group opinion favoured curricular prioritisation based on a range of clinical indicators. Applying a prioritisation based on exit examination content was not supported. Conclusion: Application of a consensus methodology incorporating free text and Likert scales allows expert opinion to be generated in relation to curricular prioritisation. This helps shape the format and educational utility of the specialty curriculum.